Service-Learning through physical-sports activities and Physical Education in university contexts with cultural diversity - CHIVA-BARTOLL, Oscar; RUIZ-MONTERO, Pedro Jesús; MARAVÉ-VIVAS, María; SALVADOR-GARCIA, Celina (Utopía y Praxis Latinoamericana, 2021)
The Service-Learning (SL) methodology provides students with a necessary scenario to learn autonomously, address social injustices and acquire professional skills. If we talk about physical activitiy and Sports (PAS) as a tool to promote the social inclusion of migrant groups and/or with cultural diversity, the benefits in the university students involved are very wide. The aim of this study is to analyze the state of the art and current situation of SL applied through PAS in various university settings that work with this type of social groups. All this, with a solid line of reasoning through a literature review with a result of ten studies, systematically selected, ranging from 2003 the oldest to 2019 the newest. In conclusion, when SL is applied in contexts targeting vulnerable groups that are culturally diverse, it comes with the development of competencies and values, as well as the acquisition of PAS related content